Input-series output-parallel full-bridge DC-DC converter for high power applications - Daoud, Guerras; Aboadla, Ezzidin Hassan Elmabrouk; Khan, Sheroz; Ahmed, Syed Faiz; Tohtayong, Majdee (Institute of Electrical and Electronics Engineers Inc., 2018)
Input-series and output-parallel (ISOP) connected DC-DC converters are suitable for high input voltage and high output current applications by using a low voltage rating power switches. This paper proposes an input-series-output-parallel Full-Bridge DC-DC converter with low-voltage switches under high frequency operation with low losses switching, low harmonic spikes with high efficiency and high power density. In this proposed work, Arduino mega microcontroller has been used to generate Pulse Width Modulation (PWM) for ISOP configuration. Under different duty cycle PWM and switching frequency, the simulation and experimental results with appropriate theoretical analysis of an ISOP full-bridge converter topology are presented.